Partial laryngectomy for naïve pT3N0 laryngeal cancer: Systematic review on oncological outcomes. Issue 1 (30th September 2022) - Campo, Flaminia; Mazzola, Francesco; Bianchi, Giulia; Manciocco, Valentina; Ralli, Massimo; Greco, Antonio; Sperduti, Isabella; de Vincentiis, Marco; Pellini, Raul
Abstract: The first aim was to define the oncologic outcomes of open partial laryngectomy (OPL) in naïve pT3 laryngeal cancer. The second aim was to analyze the outcomes after OPL versus total laryngectomy (TL). A literature search was conducted in three databases (MEDLINE, EMBASE, and Cochrane Library) until January 2022. In 805 patients treated with OPL, 5‐year OS, DSS, DFS and LFS were 80.5% (95% CI 70.6–87.6), 83.4% (95% CI 75.7–89), 77.4% (95% CI 66.3–85.7) and 77.9% (95% CI 68.7–85), respectively. Three articles compared TL versus OLP: 5‐year OS, DSS and DFS risk difference were 0.100 (95% CI −0.092 to 0.291), 0.067 (95% CI −0.085 to 0.220) and 0.018 (95% CI −0.164 to 0.201) respectively. OPL for selected pT3 laryngeal cancer is able to guarantee a high percentage of oncological success. Accurate patient selection is of utmost importance to differentiate advanced disease amenable to conservative surgery.